Kejriwal - Redefining Indian politics - Satish, D.; Kumar, M.V. Nagendra (2014)
With its promise to weed out corruption from public life, Arvind Kejriwal’s Aam Aadmi Party (AAP, Common Man Party) captured the imagination of millions of Indians. So much so that his one-year-old party was catapulted to power after the December 2013 elections in the state of Delhi (India). With a well worked out strategy which included a promise to introduce a bill which made everyone in the government including the prime minister accountable, Kejriwal’s AAP party projected itself as an alternative to the existing political parties which were known for deep-rooted corruption. Working closely with the grass-roots, formulating manifestos for each and every constituency, taking the opinion of the people on every major decision, taking the use of social media to a totally new level, AAP gained tremendous popularity among the voters. Having formed the government, it now remains to be seen how it will achieve its promises, which according to its critics, were impossible to fulfill.